2012
DOI: 10.4049/jimmunol.1103169
|View full text |Cite
|
Sign up to set email alerts
|

Homing and Adhesion Patterns Determine the Cellular Composition of the Bone Marrow Plasma Cell Niche

Abstract: According to commonly held concepts, plasma cell (PC) longevity in bone marrow (BM) depends upon their access to survival niches. These are thought to exist in nursery cell types, which support PCs by secreting PC survival factors. To better define PC survival niches and their functioning, we adoptively transferred traceable Blimp-1-GFP PCs into recipient mice lacking a proliferation-inducing ligand (APRIL), IL-6, or macrophage migration inhibitory factor. Transferred BMPCs were preferentially associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 42 publications
(59 reference statements)
2
101
1
Order By: Relevance
“…Stromal cells do not express BAFF or APRIL themselves, and it is obvious that those ligands of BCMA, the second essential survival signal for memory plasma cells, have to be provided by other cells, which we have termed “accessory” cells of the niche. Eosinophilic granulocytes,51 basophilic granulocytes,52 megakaryocytes,53 and monocytic cells54 have been described as accessory niche cells. Priorities and redundancies among these cell types have not finally been resolved 55, 56.…”
Section: Conditional Survival Of Memory Plasma Cells—the Memory Nichementioning
confidence: 99%
“…Stromal cells do not express BAFF or APRIL themselves, and it is obvious that those ligands of BCMA, the second essential survival signal for memory plasma cells, have to be provided by other cells, which we have termed “accessory” cells of the niche. Eosinophilic granulocytes,51 basophilic granulocytes,52 megakaryocytes,53 and monocytic cells54 have been described as accessory niche cells. Priorities and redundancies among these cell types have not finally been resolved 55, 56.…”
Section: Conditional Survival Of Memory Plasma Cells—the Memory Nichementioning
confidence: 99%
“…According to cell division studies, only 50-70% of bone marrow PCs appear to be long-lived (27), indicating the existence of another determining factor. Indeed, within the last 3 y, several in vivo studies demonstrated the contribution of hematopoietic cells such as megakaryocytes (27), eosinophils (28), basophils (29,30), dendritic cells and monocytes/ macrophages (14), myeloid progenitors (31), neutrophils (15), and monocytes (22) to the PC niche. In vitro, osteoclasts also stimulate PC survival (32).…”
mentioning
confidence: 99%
“…Whereas the large majority of MPCs are localized in the bone marrow (5,12), LLPCs are also found in lymphatic organs such as spleen (13), lymph nodes (14), mucosa-associated lymphatic tissues (15), as well as in chronically inflamed tissues such as the synovium in rheumatoid arthritis (16), the CNS in induced multiples sclerosis (17), the kidneys in systemic lupus erythematosus (SLE) (18), the salivary glands in Sjögren's syndrome (19), or the lung during chronic airway inflammation in allergy/asthma (20,21). In secondary lymphatic tissues, PCs reside in extrafollicular areas such as the lamina propria of mucosa and the red pulp of spleen, and LLPCs are associated with APRIL, BAFF, and IL-6 sources in the vicinity (14,15,22,23). Whereas APRIL is produced by several cell types in the bone marrow (24), only few cells in specific areas (e.g., the subepithelium zone in tonsillar crypts or intestinal villi in the mucosa) secrete this survival factor in other organs (15).…”
mentioning
confidence: 99%
“…APRIL-deficient mice or mice deficient in BCMA, the high affinity receptor of APRIL, show a significantly lower number of plasma cells in the BM than WT mice [130,131]. In addition, plasmablasts transferred into APRILdeficient mice home normally in the BM but the maintenance of long-lived plasma cells is impaired [129] and blockade of BAFF and APRIL by fusion proteins significantly reduced the plasma cell numbers in the BM [130]. The relevance of APRIL for the survival of plasmablasts and plasma cells is also shown because SLE patients contain numerous plasma cells whose survival is controlled by autocrine expression of APRIL in the self plasma cells [132].…”
Section: The Other Niches Of Adult Bone Marrowmentioning
confidence: 99%
“…The relevance of these cell types for plasmablast colonization of the BM was evidenced in Eos deficient ∆dbl GATA-1 mice in which plasmablasts migrate normally, but only a few are retained and mature to plasma cells. Importantly, the BM stroma in these mutants is normal indicating that VCAM-1+CXCL12+stromal cells are not sufficient to retain and presumptively to allow plasmablast differentiation [128,129].…”
Section: The Other Niches Of Adult Bone Marrowmentioning
confidence: 99%